Resource accountability: Enforcing state responsibilities for sufficient and equitable resources used effectively to provide all students a quality education - David G. Sciarra; Molly A. Hunter (Arizona State University, 2015)
Darling-Hammond, Wilhoit, and Pittenger (2014) addressed the need for states to align their accountability systems with new college- and career-ready learning standards. The authors recommended a new accountability paradigm that focuses on 1) meaningful learning, enabled by 2) professionally skilled and committed educators, and supported by 3) adequate and appropriate resources. This paper explicates the provision of adequate and appropriate resources, the third of these three pillars of a comprehensive approach to accountability. Adequate resources, effectively used, are prerequisites to building the capacity of schools to deliver the two other pillars, professionally skilled and committed educators and meaningful learning. Also, the effective use of public school funding is an oft-ignored but crucial step toward ensuring equal educational opportunity for all students.